Coconut. - Mohammed Nazrim Marikkar, Jalaldeen; Madurapperuma , W. S. (Wiley-BlackWell, 2012)
Coconut palm (Cocos nucifera L) is an important perennial crop distributed in most parts of the Asia and the pacific region, and some parts of America. Coconut exists in two major classes, which are typically recognized on the basis of stature: Tall and Dwarf. Cross-breeding between Tall and Dwarf types of coconut has led to the generation of many hybrid coconut varieties. Hybrids with high yield potential and attractive agronomical traits are grown commercially for harvesting either tender nuts or mature nuts. Tender nuts with the maturity stage of 7-8 months are freshly used for drinking or preserved under cold storage for future uses. Mature coconuts are mainly used for obtaining kernel, which is a base material for coconut milk as well as a host of other products. As coconut kernel is composed of lipids, proteins, carbohydrates, minerals, and vitamins, it could be a wholesome food, which can supplement the daily dietary requirement of people.